Chemical Composition and Effects of Blended Essential Oil on Humans - Tapanee Hongratanaworakit, Pongpat Srimuang, Ampot Wichanpreechar, Tharada Akarapattaranithi, Benjaporn Taorang, Pimtida Rawdlaurh (Journal of Applied Pharmaceutical Science, 2017)
The blended essential oil was composed of eucalyptus, rosemary, patchouli, and pine oils. The blended oil was analyzed by GC-MS. The effects of blended oil on autonomic parameters and emotional changes in humans following inhalation were an investigation in this study. Thirty healthy volunteers participated in this study. Autonomic parameters, i.e. systolic blood pressure, diastolic blood pressure, mean arterial pressure and pulse rate were recorded. Additionally, emotional changes were assessed by means of visual analog scale. A quasi-experimental with one group pretest-post-test design was used to compare the differences in ANS parameters and emotional changes. Data was analyzed using paired t-test. The blended oil mainly contained 1,8-cineole (33.8%), camphor (14.2%), and α-pinene (12.2%). The blended oil showed significant increases in systolic blood pressure, diastolic blood pressure, mean arterial blood pressure and pulse rate which indicated an increase of autonomic arousal. In addition, inhalation of the blended oil led to activation at the behavioral level, i.e. subjects feel more alert, more vigorous, and more cheerful than before the administration of the oil. This finding points towards an increase of arousal in terms of self-evaluation. Thus, the effects of blended oil by inhalation may be characterized by the concept of stimulating/activating effects.
Keywords: Aromatherapy, Mental stimulation, Eucalyptus, Rosemary, Pine, Patchouli.